PENGELOLAAN DATA PENYANDANG MASALAH KESEJAHTERAAN SOSIAL MENGGUNAKAN MICROSOFT ACCESS 2007 - Amalia Almas Janani; Danis Imam Bachtiar (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2017)
The system of information needed by the government agencies to process data becomes information, so that the various parties to make a good. Management of the data PMKS still conducted in manual namely using Microsoft Excel 2007. It can inhibit and complicated in search of the data, it also need a long time. Based on the description of the author did use a technique observations, collecting data in the form of an interview and study pustaka. The writer designimg a system data management PMKS using Microsoft Access 2007 because this program is easy to learn. To design of the system management of the data PMKS can simplify the increase, remove and scored the data PMKS. The purpose of writing a report final this is to implementation data PMKS at the District Office Kutoarjo using Microsoft Access 2007. Keywords: The informations, PMKS, the District Office Kutoarjo